Anatomic Peculiarities Associated with Axial Elongation of the Myopic Eye - Jonas, Jost B.; Bikbov, Mukharram M.; Wang, Ya-Xing; Jonas, Rahul A.; Panda-Jonas, Songhomitra (Journal of clinical medicine, 2023)
Purpose: To describe anatomical peculiarities associated with axial elongation in the human myopic eye. Methods: Reviewing the results of previous histomorphometrical investigations of enucleated human globes, as well as reviewing findings obtained in population-based studies and hospital-based clinical investigations of myopic patients and non-myopic individuals. Results: Myopic axial elongation is associated with a change from a mostly spherical eye shape to a prolate ellipsoid form. It is combined with choroidal and scleral thinning, most pronounced at the posterior pole and less pronounced in the fundus midperiphery. In the fundus midperiphery, the retina and density of the retinal pigment epithelium (RPE) and photoreceptors decrease with a longer axial length, while in the macular region, retinal thickness, RPE cell density, and choriocapillaris thickness are not related to axial length. With axial elongation, a parapapillary gamma zone develops, leading to an enlargement of the optic disc-fovea distance and a decrease in angle kappa. Axial elongation is also correlated with an increase in the surface and volume of Bruch’s membrane (BM), while BM thickness remains unchanged. Axial elongation causes moderately myopic eyes to show a shift of BM opening to the foveal direction so that the horizontal disc diameter becomes shorter (with a consequent vertical ovalization of the optic disc shape), a temporal gamma zone develops, and the optic nerve exit takes an oblique course. Features of high myopia are an enlargement of the RPE opening (myopic parapapillary beta zone) and BM opening (secondary macrodisc), elongation and thinning of the lamina cribrosa, peripapillary scleral flange (parapapillary delta zone) and peripapillary choroidal border tissue, secondary BM defects in the macular region, myopic maculoschisis, macular neovascularization, and cobblestones in the fundus periphery. Conclusions: These features combined may be explained by a growth in BM in the fundus midperiphery leading to axial elongation.